Using assessment results for career development career counseling : a holistic approach - Zunker, Vernon G. 1927-; Osborn, Debra S. 1968-. (Belmont, Calif. Brooks/Cole Cengage Learning, 2012)
"An excellent resource in both career development and tests and measurement courses, Using Assessment Results for Career Development, 8e vividly illustrates how to use assessment instruments to increase clients' self-awareness and help them make rational career choices. Extremely practical, this hands-on worktext delivers detailed information on applying knowledge of tests and measurements in clinical settings and using assessment results in a wide variety of counseling situations. Through case studies, charts, bulleted/numbered lists, dialogues, agency addresses, and more, students learn to truly master the use of assessment results."--Publisher's website.
A conceptual model for using assessment results -- Interpreting assessment results -- Some measurement concepts -- Ethics and career assessment. -- Aptitude and achievement tests -- Interest inventories -- Personality inventories -- Career decision inventories -- Computer-assisted career guidance and online career assessments -- Card sorts and other non-standardized assessment approaches -- Combining assessment results.
Osborn's name appears first in the 7th ed.
Osborn's name appears first on the cover of the 8th ed.
Keywords: Vocational guidance; Occupational aptitude tests; Vocational interests